Mental Disorders among College Students in Vietnam: Evidence for Improving Coping Strategies - Quang Vo, Dr.Trung (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Mental disorders are highly prevalent worldwide, especially among university students. Aims: This study therefore aimed to explore the association between various demographic characteristics and depression, anxiety disorder, and stress. Materials and Methods: A cross-sectional study was conducted from September 2016 to June 2017 among college students in Southern Vietnam. The depression, anxiety, and stress scales (DASS-21) were used to measure the severity of the core symptoms of depression, anxiety, and stress. Statistical Analysis Used: The DASS-21 were used to measure the severity of the core symptoms of depression, anxiety, and stress. Results: There were 965 participants included in this study, with the study population comprising 53.6% of medical students and 46.4% of non-medical students. Based on the study findings, 928 students (96.2%) perceived the symptoms of the three disorders (i.e., depression, anxiety, and stress), while 307 students (31.8%) suffered an extremely severe level of the three disorders. In terms of depression, the participants’ study plan (χ2 = 10.284, P = 0.001) and internet usage (χ2 = 6.076, P = 0.001) had a significant effect. For anxiety, the participants’ study plan (χ2 = 6.091, P = 0.013) and school year (χ2 = 3.629, P = 0.046) were found to have an association. With regard to stress, the participants’ field of study (χ2 = 5.900, P = 0.015), school year (χ2 = 5.102, P = 0.013), study plan (χ2 = 6.776 P = 0.009), and internet usage (χ2 = 11.807, P = 0.001) all proved to be influential. Conclusions: Coping strategies for psychological problems are hence recommended to focus on the study plans and internet usage of students.